Analysis of relationship of high fat mass and low muscle mass with lipid profile in Brazilians aged 80 years or over - Santos, Vanessa Ribeiro dos [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Gomes, Igor Conterato; Viezel, Juliana [UNESP]; Freitas, Ismael Forte [UNESP]; Gobbo, Luís Alberto [UNESP] (Elsevier, 2017)
Aim To analyze the lipid profile of older people aged ≥80 years according to body composition (high fat mass, low muscle mass and both). Material and method: The sample consisted of 113 older people aged ≥80 years. The assessment of body composition was made using Dual Energy X-ray Absorptiometry (DXA) and the lipid profile analysis using an enzymatic colorimetric kit. We used Analysis of Variance (ANOVA) test to compare the mean of lipid profile according to body composition and were constructed logistic regression models to verify the association between these two variables. Results It was found that older people with high fat had higher mean values of TG compared to normal and low muscle mass group. Older people with low muscle mass showed mean values of LDL-c lower than other groups. It was observed that older people with high fat is more likely to have (OR 2.70; 95%CI 1.14-6.37) high blood concentration of TG. Conclusion Thus, it appears that high fat is related to the high blood concentration of TG in older people aged ≥80 years, especially those with Asian origin and diabetes besides those with low muscle mass shows lower mean values of LDL-c.
Keywords: 80 and over; Aged; Lipids; Obesity; Sarcopenia